Lyoluminescence Dosimetry of L-Proline Incorporated of Sensitizer Dependence on the Temperature and pH of Solution - Abdulqader, Qahtan Adnan; Alhasan, Ammar Mohammed (Iraqi Journal of Science, 2019)
To increase the sensitivity of dosimeter, it has to improve the properties that are required to increase its sensitivity. It was proven that the dependence of lyoluminscence (LL) of irradiated amino acid (L-prolin) incorporated with chemiluminscence reagent (luciginine) on the pH and temperature of the solution. LL means the emission of light from dissolved material in a suitable solvent, which is previously exposed to ionizing radiation. When the incorporated phosphor irradiated to gamma rays an electronically excited species are trapped within the solid matrix, this extra energy will be emitted in the form of light ( 420-500nm), on dissolving the material in water in this test. The LL intensity increases with increasing pH of the solution. The best reproducible and optimum LL intensity is at (pH=8.5-9) of the solution, However, LL intensity will be decreased when the PH is higher than 12. In this value of pH the stability of free radicals is optimum. The same is found for solvent temperature dependence, the optimum LL intensity is at 45-48 oC. LL intensity will increase up to 70 oC,it was found that the total glow increased because of increasing the self-glow of luciginine , but LL intensity will decrease because of dissociation of phisphore structure. In addition to the self-glow of the sanitizer will increase too at temperate up to 70 oC , however, that will cause self-glow to the dosimeter material.